2019
DOI: 10.3389/fnagi.2019.00195
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Mitochondrial Degradome by the TAILS Proteomics Approach in a Cellular Model of Parkinson’s Disease

Abstract: Parkinson’s disease (PD) is the second most frequent neurodegenerative disease worldwide and the availability of early biomarkers and novel biotargets represents an urgent medical need. The main pathogenetic hallmark of PD is the specific loss of nigral dopaminergic neurons, in which mitochondrial dysfunction plays a crucial role. Mitochondrial proteases are central to the maintenance of healthy mitochondria and they have recently emerged as drug targets. However, an exhaustive characterization of these enzyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…The authors have identified eleven mitochondrial proteins with altered proteolytic processing, and one of these proteins, the 39S ribosomal protein L38, was cleaved by the neprilysin protease. In this study, for the first time, neprilysin has been identified as a protease linked with mitochondrial dysfunction upon the pathogenesis of Parkinson's disease, suggesting exploring targets of neprilysin as candidate biomarkers of PD (Lualdi et al, 2019).…”
Section: Terminal Amine Isotope Labeling Of Substratesmentioning
confidence: 88%
See 1 more Smart Citation
“…The authors have identified eleven mitochondrial proteins with altered proteolytic processing, and one of these proteins, the 39S ribosomal protein L38, was cleaved by the neprilysin protease. In this study, for the first time, neprilysin has been identified as a protease linked with mitochondrial dysfunction upon the pathogenesis of Parkinson's disease, suggesting exploring targets of neprilysin as candidate biomarkers of PD (Lualdi et al, 2019).…”
Section: Terminal Amine Isotope Labeling Of Substratesmentioning
confidence: 88%
“…In another study, TAILS has been applied to profile the mitochondrial N-terminome and identify candidate mitochondrial protease activated by dopamine dysregulation in neuroblastoma cells during the early stages of Parkinson's disease (PD) (Lualdi et al, 2019). The authors have identified eleven mitochondrial proteins with altered proteolytic processing, and one of these proteins, the 39S ribosomal protein L38, was cleaved by the neprilysin protease.…”
Section: Terminal Amine Isotope Labeling Of Substratesmentioning
confidence: 99%
“…Neuroblastoma could differentiate into mature neurons when stimulated by a good differentiation inducer. Studies have shown that neurons are terminally differentiated cells that are completely dependent on OXPHOS for their energy and that mitochondrial dysfunction causes neuronal cells to tend to die [ 24 ]. Our study examined the phenotypes of CHA-induced differentiation cells, demonstrating that differentiated cells lost the malignant potential of tumor cells, including reduced proliferation ability, cycle arrest in the G0/G1 phase, and decreased migration and invasion ability.…”
Section: Discussionmentioning
confidence: 99%
“…Dysfunction of these proteins not only impairs mitochondrial protein translation but also causes primary mitochondrial respiratory chain activity deficiencies and clinical diseases, such as neurodegenerative diseases ( Lopez Sanchez et al, 2021 ), inflammatory disorders ( Gopisetty and Thangarajan, 2016 ) as well as aging ( Molenaars et al, 2020 ). A study has found that MRPL49 shows altered proteolytic processing by dopamine treatment in Parkinson’s disease ( Lualdi et al, 2019 ). In addition, decreased expression of MRPL12 could reduce mitochondrial OXPHOS in proximal tubular epithelial cells ( Gu et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%